ANALISIS KUALITAS WEBSITE SICEPAT EXPRES DENGAN METODE WEBQUAL 4.0 - Rifani Nur Afiani Kamil; Anie Yoraeni - Universitas Nusa Mandiri (APMMI - Asosiasi Profesi Multimedia Indonesia, 2022)
Abstract - The Sicepat Express website can be accessed by users using mobile phones, laptops, etc. while still connected to the internet network, with the Sicepat Express website it is very easy for users to do things such as: Check Postage, Check Receipts, Contact Contacts, Service Services, Career info , location info and can see the website page. The problems that exist on the Sicepat Express website sometimes occur when users want to enter and want to access website pages a little longer. This study aims to determine the quality of the Sicepat Express website that has been accessed by users by measuring web quality using the WebQual 4.0 method. The results obtained after testing have been carried out on the validity test on each dimension, namely: Usability Quality, Information Quality, Interaction Quality and Overall Impression. For the r table value, which is 0.167 with a sample size of 98 for the r table value, it is obtained using the formula d(f) = n-2, then the result becomes 96 or 0.167 for the r table value, it can be concluded that the calculated r value of each each item is greater than the value of r table can be considered valid or reliable. And after getting the results of the validity test after that, doing the reliability test from the results of the reliability test data, it can be seen the Cronbach's Alpha value from the dimensions and WebQual 4.0 methods, namely: Usability Quality (X1) of 0.984, Information Quality (X2) of 0.982, Interaction Quality (X3 ) is 0.976, and the Overall Impression (Y1) is 0.984. From this value, it can be concluded that the Cronbach's Alpha value is > from the limit of 0.6 so that all items can be considered valid or reliable. Keywords: Website, Quality, WebQual 4.0 Method, Analysis Abstrak - Website Sicepat Expres dapat di akses oleh pengguna(user) dengan menggunakan handphone,laptop dll selagi masih terkoneksi dengan jaringan internet, dengan adanya website Sicepat Expres sangat mempermudah pengguna dalam melakukan seperti : Cek Ongkir, Cek Resi, Menghubungi Contact, Layanan Service, info Career, info lokasi serta bisa melihat halaman website nya. Adapun permasalahan yang ada pada website Sicepat Expres yang kadang – kadang terjadi saat pengguna ingin masuk dan ingin mengakses halaman website sedikit lama. Dalam penelitian ini bertujuan untuk mengetahui kualitas website Sicepat Expres yang telah di akses oleh pengguna dengan melakukan pengukuran kualitas web menggunakan metode WebQual 4.0. Hasil yang diperoleh setelah melakukan pengujian telah dilakukan pada uji validitas pada masing – masing dimensi yaitu : Usability Quality, Information Quality, Interaction Quality dan Overall Impression . Untuk nilai r table nya yaitu 0,167 dengan jumlah sampel 98 untuk nilai r table nya diproleh mengunakan rumus d(f) = n-2 maka hasil nya menjadi 96 atau 0,167 untuk nilai r table nya, maka dapat disimpulkan bahwa nilai r hitung dari masing - masing item lebih besar dari nilai r table bisa di anggap valid atau reliabel. Dan setelah mendapatkan hasil dari pengujian validitas setelah itu melakukan pengujian reability dari hasil data uji reability dapat diketahui nilai Cronbach’s Alpha dari dimensi dan metode WebQual 4.0 yaitu : Usability Quality (X1) sebesar 0,984, Information Quality (X2) sebesar 0,982, Interaction Quality (X3) sebesar 0,976, dan Overall Impression (Y1) sebesar 0,984. Dari nilai tersebut dapat disimpulkan bahwa nilai Cronbach’s Alpha > dari batasan 0,6 sehingga semua item bisa dianggap valid atau reliabel. Kata Kunci : Website, Kualitas, WebQual 4.0, Metode, Analisis